Influence of Cu addition on transformation temperatures and thermal stability of TiNiPd high temperature shape memory alloys. (May 2019) - Rehman, Saif ur; Khan, Mushtaq; Khan, A Nusair; Alam, Khurshid; Jaffery, Syed Husain Imran; Ali, Liaqat; Khan, Ashfaq
In this research, four high temperature shape memory alloys, Ti50 Ni25-x Pd25 Cux (x = 0, 5, 10 and 15) were developed and designated 0Cu, 5 Cu, 10 Cu, and 15Cu, respectively. The effect of 5%, 10%, and 15% (all in atomic percent) Cu addition was investigated through their microstructure analysis, transformation temperatures and thermal stability. After the alloying of Cu content in their desired percentage, the alloys were named as 0Cu, 5Cu, 10Cu and 15Cu alloys. The martensite onset temperature Ms of ternary 0Cu alloy increased by 12.5 ℃, 27.5 ℃ and 60.5 ℃, respectively, by replacement of Ni with 5%, 10% and 15% Cu. Similarly, the austenite finish temperature Af increased by 11 ℃, 25 ℃, and 52 ℃, respectively. At the same time, thermal hysteresis of the 5Cu, 10Cu, and 15Cu alloys decreased by 1.5 ℃, 2.5 ℃, and 8.5 ℃, respectively, as compared to 0Cu alloy. The thermal stability of ternary 0Cu alloy was improved by replacing Ni with Cu. During thermal cycling, the net drop in Ms and Af of 0Cu alloy was 7.5 ℃ and 14 ℃, respectively. By replacing Ni with 5%, 10%, and 15% Cu, the net drop in Ms decreased to 5 ℃, 3.7 ℃, and 3 ℃, respectively, whereas the net drop in Af decreased to 10 ℃, 8.7 ℃, and 5 ℃. The overall results suggested that by the addition of 5%, 10%, and 15% Cu in place of Ni in TiNiPd alloys, the transformation temperatures and thermal stability improved. At the same time, thermal hysteresis decreased to a reasonable level which has a positive effect on the actuation behavior.